Implementasi Nilai-Nilai Konstitusi dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Sebagai Upaya Penguatan Kesadaran Berkonstitusi pada Generasi Muda - Joesa Yolandari; Nabila Diani Putri; Yola Nurhidayatullah; Evitri Aulia; Tesa Arwin; Yulfa Meidita (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze the implementation of constitutional values in the 1945 Constitution of the Republic of Indonesia as an effort to strengthen constitutional awareness among the younger generation. The study used a library research method with a qualitative descriptive approach that focused on the study of various scientific sources, laws and regulations, and literature relevant to the research theme. Data were collected through documentation techniques and analyzed using content analysis to obtain a comprehensive understanding of constitutional values and their implementation in the lives of the younger generation. The results show that the 1945 Constitution of the Republic of Indonesia contains constitutional values including democracy, popular sovereignty, human rights, justice, equality before the law, unity, and citizen responsibility, which are the foundation of national and state life. Constitutional awareness plays a very important role for the younger generation because it can shape the character of democratic citizens, obey the law, respect diversity, and be able to exercise their rights and obligations responsibly. The implementation of constitutional values can be realized through an attitude of tolerance, participation in democratic life, compliance with the law, and the wise use of technology and digital media in accordance with constitutional principles. Furthermore, strengthening constitutional awareness among the younger generation requires synergy between civic education, families, communities, youth organizations, and the government through various educational programs that adapt to the developments of the digital era. This will help shape a generation of young people with integrity, a strong commitment to nationalism, and an active role in maintaining democracy, unity, and the rule of law in Indonesia.